2007
DOI: 10.1378/chest.132.4_meetingabstracts.600
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Particles Alter the Alveolar Epithelial Barrier via a Decrease in the Tight Junction Protein Occludin

Abstract: PURPOSE:To determine whether exposure of the alveolar epithelium to airborne particles alters alveolar barrier function and decreases tight junction proteins. METHODS:Rat alveolar type II cells (ATII) were cultured on transwells inserts, and lung adenocarcinoma A549 on 100 mm culture dishes. These cells were exposed to particulate matter < 10 microns in diameter (PM10) (1,5 ,10 and 20 μg/cm 2 ) or vehicle for up to 24 hours, after which the plasma membranes were isolated and examined using immunofluorescence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…TJ proteins are very dynamic and change their location when the permeability of the epithelial monolayer is changing [ 37 , 38 ]. Yshii and colleagues [ 39 ] exposed mice as well as in vitro cultured alveolar epithelial cells to PM10 and demonstrated a decrease in the total abundance of occludin. They also observed that connections of occludin with the protein zonula occludens-1 were altered.…”
Section: Discussionmentioning
confidence: 99%
“…TJ proteins are very dynamic and change their location when the permeability of the epithelial monolayer is changing [ 37 , 38 ]. Yshii and colleagues [ 39 ] exposed mice as well as in vitro cultured alveolar epithelial cells to PM10 and demonstrated a decrease in the total abundance of occludin. They also observed that connections of occludin with the protein zonula occludens-1 were altered.…”
Section: Discussionmentioning
confidence: 99%